Role of Homoeopathy in Managing Chronic Paronychia: A Pretest–Posttest Interventional Study - Choubey, Gurudev; Nahar, Laijun; Purkait, Rajib; Banerjee, Abhiram; Roja, Varanasi (Homœopathic Links, 2022)
Background Chronic paronychia (CP), one of the commonest recalcitrant nail disorders, is a troublesome source of considerable discomfort to the patients, which negatively affects the quality of life (QoL) mainly of the housewives reporting in the Indian subcontinent.Objective The aim of this study is to assess the utility of individualised homoeopathic treatment (IHT) in managing painful episodes with the improvement in QoL of CP patients.Method A pretest–posttest clinical study was conducted on 40 patients with CP. The Numeric Rating Scale (NRS) and Dermatology Life Quality Index (DLQI) were the outcome measures, assessed at baseline and after 2 months of IHT. Modified Naranjo Criteria (MNC) evaluated the possible causal attribution of IHT.Results There was a statistically significant reduction in pain NRS score (8.89 ± 0.84 vs 2.97 ± 1.17; 95% confidence interval [CI] = 5.44–6.39; p < 0.01) as well as DLQI score (19.35 ± 2.95 vs 3.59 ± 1.99; 95% CI = 15.06–16.45; p < 0.01) among 37 patients. The large effect size derived (4.17) clinically, substantiates the beneficial effects in managing the painful episodes of CP. The MNC scores (7–10) ascertained the likelihood of improvement due to IHT.Conclusion IHT significantly reduced the pains due to CP and improved the QoL. Further studies are warranted with enhanced methodology.
Keywords: paronychia; homoeopathy; pain; quality of life